Fat-free mass, metabolically healthy obesity, and type 2 diabetes in severely obese asian adults - Pornpoj Pramyothin (2018)
Copyright © 2017 AACE. Objective: To determine whether fat free mass (FFM) is independently associated with the metabolically healthy obesity (MHO) phenotype, the metabolic syndrome (MS), and type 2 diabetes (T2D) in obese Asian adults. Methods: Obese patients (body mass index BMI ≥25 kg/m2) seeking weight management at an academic medical center from 2007 to 2016 were included. FFM was measured by bioelectrical impedance. Results: Of the 552 patients (67.0% female, median age 40.5 years, median BMI 38.3 kg/m2), MHO was present in 19%, MS in 55.4%, and T2D in 32.6%. In multivariate models, higher fat-free mass index (FFMI) was independently associated with the metabolically abnormal obesity (MAO) phenotype, (odds ratio OR 1.22, 95% confidence interval CI 1.09-1.37), and increased risk of MS (OR 1.12, 95% CI 1.03-1.22) in women but not in men. Older age was independently associated with the MAO phenotype (OR 1.06, 95% CI 1.04-1.09 in women; OR 1.06, 95% CI 1.02-1.09 in men), MS (OR 1.05, 95% CI 1.03-1.06 in women; OR 1.05, 95% CI 1.02-1.07 in men), and T2D (OR 1.07, 95% CI 1.05-1.09 in women; OR 1.06, 95% CI 1.04-1.09 in men). Waist-hip ratio was independently associated with the MAO phenotype in men (OR 1.08, 95% CI 1.01-1.15), while waist circumference was associated with T2D in women (OR 1.03, 95% CI 1.01-1.05). Conclusion: Older age, central fat distribution, and-in contrast to previous findings-An increase in FFMI among women were independent predictors of adverse metabolic health in this cohort of middle-Aged obese Asian adults. Further studies are required to elucidate underlying mechanisms and therapeutic implications of these findings.